4x+1=6x+3

Simple and best practice solution for 4x+1=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+1=6x+3 equation:


Simplifying
4x + 1 = 6x + 3

Reorder the terms:
1 + 4x = 6x + 3

Reorder the terms:
1 + 4x = 3 + 6x

Solving
1 + 4x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
1 + 4x + -6x = 3 + 6x + -6x

Combine like terms: 4x + -6x = -2x
1 + -2x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
1 + -2x = 3 + 0
1 + -2x = 3

Add '-1' to each side of the equation.
1 + -1 + -2x = 3 + -1

Combine like terms: 1 + -1 = 0
0 + -2x = 3 + -1
-2x = 3 + -1

Combine like terms: 3 + -1 = 2
-2x = 2

Divide each side by '-2'.
x = -1

Simplifying
x = -1

See similar equations:

| 3(-4w)-6w=9 | | w^2-4w=16+2w | | a-1=4 | | 7(x+2)-9=5 | | -1/3(3x+9)-10x=-2x+4 | | 35*x=7 | | 13x+14=3x+314 | | 65+30k=50k+85 | | 2(x+4)=2(x-4)+4 | | -11(1+5x-2)=-3(12b-9) | | y=.5*.8+2 | | 102-7x=29x+18 | | 3(x-6)=2(x-4) | | -4(x-3)-3=9 | | n+5=27 | | u/3=9 | | -2y+4=-2(3y+6) | | 8-9x=32-30x | | 66-7x=2x+18 | | 2a-10=12 | | .5x+2=-2x+4 | | 12.7-18.5+15+6.3-1+28.5= | | 3x-17+5x=7x+10 | | 12-9x=132-30x | | 15.8=16+0.2n | | 0.7x-3.1=0.4 | | 5w=8 | | 5(2c-3)=4c+9 | | -11(1+5b)=-3(12b-9) | | -5=v-4 | | r=5in | | -8y-5=2y-10 |

Equations solver categories